EFEKTIVITAS PENYALURAN BANTUAN LANGSUNG TUNAI DANA DESA DI DESA SINDANGGALIH KECAMATAN CIMANGGUNG KABUPATEN SUMEDANG - Ahmad Sopiyandi (JRPA - Journal of Regional Public Administration, 2026)
This study aims to determine the effectiveness of the distribution of Direct Cash Assistance from Village Funds in Sindanggalih Village, Cimanggung District, Sumedang Regency, identify the factors hindering the distribution of this assistance, and evaluate the efforts made to overcome these obstacles. This study employs a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The results of the study indicate that the distribution of BLTDD has been carried out fairly effectively and in accordance with procedures, although there are still some challenges in its implementation. The main obstacles identified include inaccuracies in targeting due to outdated databases, insufficient programme socialisation to the community, delays in fund disbursement due to complex bureaucracy, and suboptimal utilisation of village information systems such as SIPEDE. To overcome these obstacles, the village government has taken several measures, such as updating recipient data through village meetings, improving coordination between agencies, strengthening socialisation, and providing training on the use of supporting applications. This study is expected to serve as a reference for village governments and related parties in improving the effectiveness of social assistance programmes in a more equitable, accountable, and targeted manner.